2017
DOI: 10.1177/1524838017719234
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of Gender-Based Violence Research in Europe: Findings From a Focused Mapping Review and Synthesis

Abstract: This article reports the findings from a new form of review: a focused mapping review and synthesis. The aim was to create a contemporary, snapshot profile of the nature and scope of gender-based violence (GBV) studies conducted in Europe. GBV is one of the most prevalent human rights violations in the world affecting mainly women and girls. The policy context of GBV in Europe has gathered momentum in recent years, but we do not have a clear picture of how this relates to research activity. Thirteen journals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
(86 reference statements)
2
15
0
3
Order By: Relevance
“…As discussed earlier, some forms of GBV are more culturally driven than others and may therefore be discussed to a greater extent in non-English language journals. That said, a recent European-focused mapping review and synthesis by Bradbury-Jones, Appleton, Clark, and Paavilainen (2019) found that IPV and sexual abuse are the GBV forms that receive the majority of literature attention, consistent with the findings here. While these two forms likely represent the largest global GBV burden, it was disappointing that no other forms featured in this review.…”
Section: Limitationssupporting
confidence: 88%
“…As discussed earlier, some forms of GBV are more culturally driven than others and may therefore be discussed to a greater extent in non-English language journals. That said, a recent European-focused mapping review and synthesis by Bradbury-Jones, Appleton, Clark, and Paavilainen (2019) found that IPV and sexual abuse are the GBV forms that receive the majority of literature attention, consistent with the findings here. While these two forms likely represent the largest global GBV burden, it was disappointing that no other forms featured in this review.…”
Section: Limitationssupporting
confidence: 88%
“…We undertook an FMRS of fitness to practice investigations involving complaints about medical misconduct. FMRS is an emerging form of review that has been used and described only recently 19–23. Unlike many other review methodologies that produce a broad and exhaustive systematic review of the literature, this review methodology reduces the breadth of a study, ensuring the research has a specific focus.…”
Section: Methodsmentioning
confidence: 99%
“…On the whole, despite minor differences, these findings indicate that the same training programme would be suitable for all three countries. The international training programme would be in accordance with a guideline that international collaboration across Europe is important to improve the longerterm well-being of parties of GBV (Bradbury-Jones et al, 2017).…”
Section: Discussionmentioning
confidence: 99%